Global research on depression among university students due to impacts of COVID-19 outbreak: A scientometric review using PubMed database - Lankathilake, M.A. (The Library, University of Colombo., 2020)
COVID-19 that emerged in the latter part of 2019, became a global pandemic by early 2020. All community groups suffered as a result, including the university students. They have been experiencing residential lockdowns, postponement of classes, delays in graduation, increased cost on connectivity and devices, loss of income etc. These issues could have adversely affected their mental health leading to depression. The aim of this study is to map the research on depression among the university students due to COVID-19, based on the articles indexed in the PubMed database. The articles related to the above topic dated from January 2020 to December 2020 were retrieved from PubMed. Accordingly, 150 search results were obtained. Out of the total number of results, seventy-five (75) articles that are directly related to the study population were selected, excluding the studies relevant to general public, primary school children, high school students, etc. The citations were saved as a csv file and exported to the Rayyan QCRI systematic review application for further support of analysis. The total number of 75 articles have been published in 50 journals. ‘International Journal of Environmental Research and Public Health’ was identified as the most productive (6 articles, 8%) journal, followed by ‘Journal of Affective Disorders’ (5 articles, 6.67%). Researches related to the topic were carried out in 28 countries. China was leading with the highest number of articles published (20 articles; 26.67%), followed by the USA (12 articles; 16%). The maximum relative growth rate of 1.1 was recorded in February, followed by 0.77 in June. The highest Doubling time is 8.31 in December, followed by 3.11 in August.
Keywords: PubMed, Scientometric Analysis, Depression, COVID-19, University Students